Eight years into the horizon of aspirational maternal and newborn health pledges: a nationwide cross-sectional exploration of the Burundian EmONC network capacity and budget deficits - Habonimana, D; Leckcivilize, A; Nicodemo, C; Nzorironkankuze, JB; Ndacayisaba, A; Bishinga, A; Ndayisenga, J; Niane, ESD; Bazikamwe, S; Ndabashinze†, P; English, M (BMJ Publishing Group, 2024)
Objective: The Burundian emergency obstetric and neonatal care (EmONC) programme, which was initiated in 2017 and supported by a specific policy, does not appear to reverse maternal and newborn mortality trends. Our study examined the capacity challenges facing participating EmONC facilities and developed alternative investment proposals to improve their readiness paying particular attention to EmONC professionals, physical infrastructure, and capital equipment. Design: Cross-sectional study. Setting: Burundian EmONC facilities (n=112). Participants: We examined EmONC policy documents, consulted 12 maternal and newborn health experts and 23 stakeholders and policymakers, surveyed all EmONC facilities (n=112), and collected cost data from the Ministry of Health and local suppliers in Burundi. We developed three context-specific EmONC resource benchmark standards by facility type; the Burundian policy norms and the expert minimum and maximum suggested thresholds; and used these alternatives to estimate EmONC resource gaps. We forecasted three corresponding budget estimates needed to address prevailing deficits taking a government perspective for a 5-year EmONC investment strategy. Additionally, we explored relationships between EmONC professionals and selected measures of service delivery using bivariate analyses and graphically. Results: The lowest EmONC resource benchmark revealed that 95% of basic EmONC and all comprehensive EmONC facilities lack corresponding sets of human resources and 90% of all facilities need additional physical infrastructure and capital equipment. Assessed against the highest benchmark which proposes the most progressive set of standards for the prevailing workloads, Burundi would require 162 more medical doctors, 1005 midwives and nurses, 132 delivery rooms, 191 delivery tables, 678 and 156 maternity and newborn care beds, and 395 incubators amounting to US$32.9 million additional budget for 5 years. Conclusion: We demonstrated that Burundian EmONC facilities face enormous capacity challenges equivalent to US$32.9 million funding gap for 5 years; averagely approximating to 5.96% total health budget increase annually.